Complete Remission in Childhood-Onset Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Children's Memorial Hospital, Chicago, IL, and Yale School of Medicine, New Haven, CT determined the probability of attaining complete remission of nonsyndromic epilepsy in a community-based cohort of 347 children with onset of epilepsy between ages of 1 month and 16 years (average, 5.5 years).